Oceanographic and biological landscapes used by the Southern Giant Petrel during the breeding season at the Patagonian Shelf - Copello, Sofía; Dogliotti, Ana Inés; Gagliardini, Domingo Antonio; Quintana, Flavio Roberto (Marine Biology)
The study of how and why marine animals distribute themselves at sea has important conservation and management implications of the species and their habitats. We characterize the oceanographic and biological landscapes of the marine areas used by breeding Southern Giant Petrels (Macronectes giganteus) at Patagonian colonies and explore inter-sexual and inter-colony diVerences. The at-sea movements of 16 adults (7 males and 9 females) were studied by means of satellite telemetry techniques during 1999, 2000, 2002, and 2004 breeding seasons. Southern Giant Petrels utilized an oceanographic scenario characterized by high productivity, warm sea surface temperature, and shallow waters. The biological landscape was characterized by a high availability of squid and carrion nearby colonies. Females spent more time in the shelf break and exploited deeper waters than males. In contrast, males spent more time in coastal areas and they showed a higher spatial overlap with areas of high squid density than females. Such a prosperous foraging scenario for both sexes may play a key role in the growth of the breeding population of Southern Giant Petrel Patagonian colonies. Fil: Copello, Sofía. Universidad Nacional de Mar del Plata; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Dogliotti, Ana Inés. Consejo Nacional de Investigaciónes Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Astronomía y Física del Espacio. - Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Astronomía y Física del Espacio; Argentina Fil: Gagliardini, Domingo Antonio. Consejo Nacional de Investigaciónes Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Astronomía y Física del Espacio. - Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Astronomía y Física del Espacio; Argentina. ...